Associative Attitude Learning: A Closer Look at Evidence and How It Relates to Attitude Models. (May 2019) - Corneille, Olivier; Stahl, Christoph
Associative attitude learning is typically viewed as a low-level process that automatically registers mere co-occurrences between stimuli, independent of their validity and relational meaning. This view invites to critically examine how attitude formation conforms to four operating conditions (i.e., unawareness, efficiency, goal independence, and uncontrollability) and two operating principles (i.e., unqualified registration of mere co-occurrences between stimuli and formation of direct stimulus–response links), which is the main purpose of the present contribution. The general discussion examines how contemporary attitude models endorse these conditions and principles. Overall, this contribution calls for (a) a nuanced understanding of the nature and scope of associative attitude learning, (b) a fine-grained understanding of how contemporary attitude models endorse conditions and principles reviewed here and find them relevant to their theorization of attitude formation, (c) a clarification of how direct and indirect evaluative measures relate to these conditions and principles, and (d) enhanced efforts in specifying contemporary attitude formation models.